A Prodrug Approach to Improve the Physico-Chemical Properties and Decrease the Genotoxicity of Nitro Compounds - Chin, Chung Man [UNESP]; Bosquesi, Priscila Longhin [UNESP]; dos Santos, Jean Leandro [UNESP] (Bentham Science Publ Ltd, 2011)
In therapeutics research, the nitro compounds are part of an important group of drugs with multiple pharmacological activities. However, in drug design, the inclusion of a nitro group in a molecule changes the physico-chemical and electronic properties and is associated with increased mutagenicity and carcinogenicity. In addition, several studies have related the relationship between the antimicrobial and/or anti-protozoal activity and the mutagenic effect to reduction of the nitro group. This work reviews the toxicity of nitro compounds and shows how the use of prodrugs can increase the biological activity and decrease the genotoxicity of nitro compounds, without any modification in nitro reduction behavior, but rather by physico-chemical improvement. Examples are given of metronidazole and nitrofurazone prodrugs.
Keywords: Prodrugs; nitro-compounds; metronidazol; nitrofurazone; genotoxicity; physico-chemical properties